PENINGKATAN AKTIVITAS SEL EPITEL PADA KASUS DENTURE STOMATITIS OLEH GEL Epigallocatechin gallate 0,5% - Nugrahini, Sintha (Faculty of Dentistry, Mahasaraswati Denpasar University, 2018)
Complete denture wearing patients are often associated with the presence of denture stomatitis. Poor-fitting dentures may increase mucosal trauma. It cause pressure on the mucosa and create a mechanical irritation. Epigallocatechin gallate(EGCG), is a flavonoid class of polyphenols antioxidant that have been widely researched, proven to have anti-inflammatory effects and may improve wound healing. The objective of this study was to prove the potential role of EGCG promoting reepithelialization of oral mucosa woundhealing.The study was a randomized Post Test Only ControlGroup Design experimental study. 32 male rats (Rattus norvegicus) were divided into 2 treatment groups. The controlgroup were given placebo gel administration (CMC-Na) for 3 days, and the treatment groups were given EGCG Gel 0.5% for 3 days. On the 6th day, mice were euthanized for tissue sampling and histological preparations, made by HE stainning. The data were analyzed using the Independent t-Test.The mean of epithelial cleft oftreatment group (549.25 ± 217.094 µm) was lower than the controlgroup (1417.25 ± 180.572 µm), it was statistically different.EGCG Gel 0.5% increaseproduction of TransformingGrowth Factor-beta 1 (TGF-β1) to stimulate migration and adhesion of epithelial cell.Thus, it is concluded that EGCG gel 0.5% enhance reepithelialization on mucosa wound healingof Denture Stomatitis.